Autophagy Hijacking in PBMC From COVID-19 Patients Results in Lymphopenia - Barbati, Cristiana; Celia, Alessandra Ida; Colasanti, Tania; Vomero, Marta; Speziali, Mariangela; Putro, Erisa; Buoncuore, Giorgia; Savino, Flavia; Colafrancesco, Serena; Ucci, Federica Maria; Ciancarella, Claudia; Balbinot, Eugenia; et al. (Frontiers in Immunology, 2022)
Autophagy is a homeostatic process responsible for the self-digestion of intracellular components and antimicrobial defense by inducing the degradation of pathogens into autophagolysosomes. Recent findings suggest an involvement of this process in severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. However, the role of autophagy in the immunological mechanisms of COVID-19 pathogenesis remains largely unexplored. This study reveals the presence of autophagy defects in peripheral immune cells from COVID-19 patients. The impairment of the autophagy process resulted in a higher percentage of lymphocytes undergoing apoptosis in COVID-19 patients. Moreover, the inverse correlation between autophagy markers levels and peripheral lymphocytes counts in COVID-19 patients confirms how a defect in autophagy might contribute to lymphopenia causing a reduction in the activation of viral defense. These results provided intriguing data that could help in understanding the cellular underlying mechanisms in COVID-19 infection, especially in severe forms.